2021
DOI: 10.1093/cdn/nzab087
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approach in Addressing Undernutrition in Developing Countries: A Scoping Review of Integrated Water Access, Sanitation, and Hygiene (WASH) + Nutrition Interventions

Abstract: A scoping review of integrated WASH plus Nutrition interventions was conducted mainly to describe different components of intervention and examine their effectiveness in improving nutritional outcomes among children. Of the eight small- to large-scale interventions, six were conducted in sub-Saharan Africa and the remaining two, in South Asia. All the interventions were done in rural settings; the majority involved sanitation and hygiene deliverables along with the nutrition strategies, such as distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Pickering et al (2019) in their interpretation paper recommended focusing on interventions that could more effectively reduce fecal contamination in domestic environments. Furthermore, as highlighted in a recent review of integrated WASH and Nutrition interventions, water access represents a key component and should be addressed properly for uptake of hygiene or sanitation practices and optimal caretaking behaviors to be easily achievable by women (Nounkeu & Dharod 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pickering et al (2019) in their interpretation paper recommended focusing on interventions that could more effectively reduce fecal contamination in domestic environments. Furthermore, as highlighted in a recent review of integrated WASH and Nutrition interventions, water access represents a key component and should be addressed properly for uptake of hygiene or sanitation practices and optimal caretaking behaviors to be easily achievable by women (Nounkeu & Dharod 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, because of the structural and immunological changes that occur in the small intestine and are associated with SAM, diarrhea accompanying SAM has been associated with an increased mortality. A recent review aiming at understanding an integrated WASHþnutrition approach and their outcomes concluded that consistent access to sufficient amounts of clean water was critical to expect a fecal-free environment and a decreased rate of diarrhea among children (Nounkeu & Dharod 2021). Especially, recommendations should be made to the Community-Based Management of Acute Malnutrition programs to always include not only soft WASH educationalrelated components (hygiene and handwashing practices) but also hardware delivery such as boreholes or latrines, in order to hope for the extent of fecal-free environment that should be attained for WASH interventions to have beneficial and significant effects on children's nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results showed that WASH was not directly related to improved growth among young children. This is not surprising, since this and previous studies [47,48] showed that to begin with, water access was a huge issue and integration of improvement of water infrastructure was critical in advancing health in rural areas. Additionally, measurement of water insecurity in WASH and other integrated trials is critical, since like food insecurity, water insecurity is experiential in nature and might not be captured by environmental indicators such as distance and time to water source.…”
Section: Plos Watermentioning
confidence: 73%
“…Such excess time cost potentially leads to the following pathways, all of which increase the odds of diarrhea occurring among infants and toddlers: (1) the prioritization of water for cooking and drinking versus for cleaning activities; (2) the reuse and recycling of water causing cross-contamination; and (3) the excess time spent on water fetching reducing time for self-care, childcare, and other wellness activities. Furthermore, our previous qualitative studies have shown that excess time spent on water fetching leads to limited water use, including the limited use of sanitation facilities, since they require regular cleaning and water use (Nounkeu & Dharod 2020). In reviewing integrated WASH and nutrition randomized trials, it was concluded that without an adequate supply of water, the uptake of sanitation and handwashing will be difficult at the household level (Bekele et al 2020).…”
Section: Discussionmentioning
confidence: 99%